Oxidative stress in mollusks Biomphalaria glabrata exposed to gamma radiation - Silva, Luanna Ribeiro Santos; Augusto, Ricielle Lopes; Siqueira, Williams Nascimento de; Pereira, Dewson Rocha; Silva, Edvane Borges da; Melo, Ana Maria Mendonça de Albuquerque (Scientia Plena, 2018)
Ionizing radiation can cause biological changes in different organisms such as mollusks from Biomphalaria glabrata species, in which alterations could be observed in the reproductive system of the specimens, prejudicing fertility and fecundity. As the changes may occur due to the lipid peroxidation caused by the action of free radicals on the gonads, the objective of this work was to evaluate the oxidative damage caused by the exposure of B. glabrata mollusks to different doses of 60Co gamma radiation. In addition, efforts were carried out to standardize a sensitive and low-cost technique for detecting negative effects caused by high doses of ionizing radiation. For this, each mollusk group (n = 10) was submitted to 0 (control), 10, 15, 20 and 25 Gy (gammacell 60Co, dose rate 3.53 kGy/h). The TBARS method was applied for the quantification of lipid peroxidation of the gonads of the mollusks after 24 and 48 h. ANOVA, followed by the mean comparison (Tukey) at the 5% of significance level (p<0.05), indicated high concentrations of TBARS in the gonads after 24 h. Otherwise, after 48 h, differences for TBARS concentrations were not significant, determining that the action of free radicals from ionizing radiation on cell membranes mainly occurred within 24 h after irradiation. Therefore, the TBARS assay could be applied for detecting oxidative stress caused by short exposure of B. glabrata to ionizing radiation.